Effect of temporal resolution on 4D flow MRI in the portal circulation. Issue 4 (28th August 2014) - Landgraf, Benjamin R.; Johnson, Kevin M.; Roldán‐Alzate, Alejandro; Francois, Christopher J.; Wieben, Oliver; Reeder, Scott B.
Abstract : Purpose: To demonstrate the use of temporal averaging with radial 4D flow magnetic resonance imaging (MRI) to reduce scan time for quantification and visualization of flow in the portal circulation. This study compared phase‐contrast MR angiography, 3D flow visualization, and flow quantification of portal venous hemodynamics of time‐averaged vs. time‐resolved reconstructions. Materials and Methods: Time‐resolved 3D radial ("4D") phase contrast data were acquired from 44 subjects (15 volunteers, 29 cirrhosis patients) at 3T. Images were reconstructed as a fully sampled time‐resolved reconstruction and multiple time‐averaged reconstructions using a variable number of acquired projections to simulate different scan times. Images from each reconstruction were evaluated to compare the quality of anatomical and hemodynamic visualization. Results: Time‐averaged reconstructions outperformed time‐resolved reconstructions for flow quantification (3.9 ± 3.1% error vs. 5.2 ± 4.4% error), average streamline length (47 ± 7 mm vs. 34 ± 15 mm), and visualization quality (average grading = 3.7 ± 0.5 vs. 2.2 ± 0.9). In addition, excellent visualization quality was achieved using fewer acquired projections. Conclusion: Reductions in scan time can be achieved through time‐averaging while still providing excellent visualization and quantification in the portal circulation. Scan time reduction of up to 70%–80% was possible for high‐quality assessment, translating into a reduction in scan time from 10–12 minutes to ∼3–4 minutes.J. Magn. Reson. Imaging 2014;39:819–826. ©2013 Wiley Periodicals, Inc .